Peningkatan Terminal Rawa Buaya Menjadi Tipe A Dengan Arsitektur Perilaku di Jakarta Barat - Anwar Sanusi; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Rawa Buaya Terminal is a cross-land transportation terminal to accommodate public transport vehicles which act as a place for regulating, monitoring and operating traffic to facilitate the flow of passengers. Rawa Buaya Terminal is also a city facility that uses behavioral architecture by considering comfort and paying attention to user needs to facilitate activities. At present the Rawa Buaya terminal will be prepared to become a type A bus terminal replacing the Kalideres terminal which is considered no longer feasible to function as a type A terminal in West Jakarta. Architecture Behavior is often used in designing a building to create a built environment by paying attention to aspects of psychology. Using the theory of Carol Simon Weisten and Thomas G. David in implementing the terminal design of Rawa Buaya pay attention to 4 points: the existence of human and environmental communication, accommodating the activities of its inhabitants, fulfilling aesthetic values, composition and form, paying attention to the conditions and behavior of building users, so that the terminal is expected to accommodate all user activities in the terminal area.